Evaluation of nitrogen availability in liquid feedstuffs - E.A. Elwakeel; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2004)
We developed an in vitro assay to assess ruminal availability of protein in liquid feeds containing soluble protein/nitrogen. Microbial mass accumulating as a result of assimilation of dietary nitrogen by ruminal microbes during an in vitro fermentation is measured. In the assay, microbial growth is most limited by the availability of protein/nitrogen, so microbial mass is proportional to the amount of available nitrogen in the sample. In liquid feeds that we generated in the laboratory, ruminal nitrogen availability decreased in response to mild heating, and the decline was greater for feedstuffs containing true protein rather than urea. Addition of salt to the products decreased nitrogen availability by an average of 21%, whereas addition of 4% phosphoric acid decreased nitrogen availability by 50%. Future research will be needed to fully characterize these effects so that negative impacts of manufacturing on protein availability can be prevented.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Nitrogen; Liquid feedstuff; rumen